Transgelin-2: A Double-Edged Sword in Immunity and Cancer Metastasis - Kim, Hye-Ran; Park, Jeong-Su; Karabulut, Hatice; Yasmin, Fatima; Jun, Chang-Duk (Frontiers in Cell and Developmental Biology, 2021)
Transgelin-2, a small actin-binding protein, is the only transgelin family member expressed in immune cells. In T and B lymphocytes, transgelin-2 is constitutively expressed, but in antigen-presenting cells, it is significantly upregulated upon lipopolysaccharide stimulation. Transgelin-2 acts as a molecular staple to stabilize the actin cytoskeleton, and it competes with cofilin to bind filamentous (F)-actin. This action may enable immune synapse stabilization during T-cell interaction with cognate antigen-presenting cells. Furthermore, transgelin-2 blocks Arp2/3 complex-nucleated actin branching, which is presumably related to small filopodia formation, enhanced phagocytic function, and antigen presentation. Overall, transgelin-2 is an essential part of the molecular armament required for host defense against neoplasms and infectious diseases. However, transgelin-2 acts as a double-edged sword, as its expression is also essential for a wide range of tumor development, including drug resistance and metastasis. Thus, targeting transgelin-2 can also have a therapeutic advantage for cancer treatment; selectively suppressing transgelin-2 expression may prevent multidrug resistance in cancer chemotherapy. Here, we review newly discovered molecular characteristics of transgelin-2 and discuss clinical applications for cancer and immunotherapy.